Tetraglyme-mediated synthesis of Pd nanoparticles for dehydrogenation of ammonia borane - Kim, Sung-Kwan; Kim, Tae-Jin; Kim, Tae-Young; Lee, Gaehang; Park, Joon T.; Nam, Suk Woo; Kang, Sang Ook (ROYAL SOC CHEMISTRY, 2012)
Palladium nanoparticles (PdNPs) were conveniently prepared in tetraglyme (TG) solution using a variety of palladium precursors. At 140 degrees C, TG promoted Pd-3(OAc)(6) to produce irregular shaped PdNPs with an average size of 4 nm. When these PdNPs were re-dispersed in TG and used for the dehydrogenation of ammonia borane (AB) at 85 degrees C, remarkably enhanced catalytic performance was achieved to release 2.3 equiv. of H-2 in 1 h.
Keywords: CHEMICAL HYDROGEN STORAGE; CATALYZED DEHYDROGENATION; REGENERATION; GENERATION; COMPLEXES; OXIDATION